Pengembangan Media Genially pada Materi Volume Kubus Dan Balok di Sekolah Dasar - Anwar, Muhfik; Murtiyasa, Budi; Hidayati, Yulia Maftuhah; Minsih, Minsih (Jayapangus Press, 2025)
This study aims to, (1) Develop the Genially learning media on the topic of volume for cuboid and rectangular prism in elementary schools, and (2) Assess the feasibility level of the Genially learning media named